A thermostable Gloeophyllum trabeum xylanase with potential for the brewing industry. (15th May 2016) - Wang, Xiaoyu; Luo, Huiying; Yu, Wangning; Ma, Rui; You, Shuai; Liu, Weina; Hou, Lingyu; Zheng, Fei; Xie, Xiangming; Yao, Bin
Highlights: An acid tolerant xylanase with an optimal temperature of 75 °C. A versatile xylanase with significant glucan and p -nitrophenol-β-cellobiose activities, which is protease resistant. Improved mashing performance of filtration rate and viscosity reduction. The mutation of Gly48 to Asp, Arg or Lys result in different temperature optima. Abstract: A xylanase gene of glycoside hydrolase family 10, Gt Xyn10, was cloned from Gloeophyllum trabeum CBS 900.73 and expressed in Pichia pastoris GS115. Purified recombinant Gt Xyn10 exhibited significant activities to xylan (100.0%), lichenan (11.2%), glucan (15.2%) and p -nitrophenol-β-cellobiose (18.6%), demonstrated the maximum xylanase and glucanase activities at pH 4.5–5.0 and 75 °C, retained stability over the pH range of 2.0–7.5 and at 70 °C, and was resistant to pepsin and trypsin, most metal ions and SDS. Multiple sequence alignment and modeled-structure analysis identified a unique Gly48 in Gt Xyn10, and site-directed mutagenesis of Gly48 to Lys improved the temperature optimum up to 80 °C. Under simulated mashing conditions, Gt Xyn10 (80 U) reduced the mash viscosity by 12.8% and improved the filtration rate by 31.3%. All these properties above make Gt Xyn10 attractive for potential applications in the feed and brewing industries.